In the Service of Christian Unity — the Ecumenical Zeal of Fr. George Florovsky and His Contribution to the Establishment of the World Council of Churches - Видовић, Јулија (Sabornost - The Theological Year-book, 2015)
Fr. George Florovsky was the theological spokesman of the Orthodox Church at the WCC in Amsterdam 1948, and was already well–known as the most significant Orthodox representative in the Ecumenical dialogue. Through this research we emphasized a few key points in the forming process of the WCC. This article is an examination of the activity of Fr. Florovsky, and an attempt to stress as much as possible his significance and impact in our time, and to point out actuality of his thought and work.